2019
DOI: 10.3390/math7020206
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Fractional Integral Operators Pertaining to the Product of Srivastava’s Polynomials and Generalized Mathieu Series

Abstract: Fractional calculus image formulas involving various special functions are important for evaluation of generalized integrals and to obtain the solution of differential and integral equations. In this paper, the Saigo’s fractional integral operators involving hypergeometric function in the kernel are applied to the product of Srivastava’s polynomials and the generalized Mathieu series, containing the factor x λ ( x k + c k ) − ρ in its argument. The results are expressed in terms of the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Inspired fundamentally by the works of Cerone and Lenard [14] (see also [16]), Srivastava and Tomovski established a generalized Mathieu series family in [17].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired fundamentally by the works of Cerone and Lenard [14] (see also [16]), Srivastava and Tomovski established a generalized Mathieu series family in [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature of fractional calculus, it is distinctly observed that the fractional integral operators and fractional integral formulas containing special functions occupied an influential place in computational and applied mathematics [19][20][21]. The fractional calculus of various types of special functions is used in many research papers [22][23][24][25]. For more details about the recent works in the field of dynamic system theory, stochastic systems, nonequilibrium statistical mechanics, and quantum mechanics, we refer the interesting readers to [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%